PENGARUH PERSONALITY DAN QUALITY OF WORK LIFE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MODERASI SERVANT LEADERSHIP (STUDI PADA DOSEN STEKOM SEMARANG) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine the influence of personality, quality of work life, towards organizational citizenship   leadership pada Dosen Stekom Semarang, from the results of regression analysis showed that personality variables (X1), quality of work life (X2) together influence on organizational citizenship behavior (Y1). With personality (X1) is the variable most positive effect on organizational citizenship behavior followed by the quality of work life. Both of these variables are able to explain Organizational Citizenship Behavior, the rest is explained by other variables outside of the model, for example, motivation, leadership and others. Results of the calculation coefficient of determination in model II shows that the Servant Leadership does not moderate the effect of variable Personality with Organizational Citizenship Behavior. Results of the calculation coefficient of determination in model III shows that the Servant Leadership does not moderate the effect of variable Quality of Work Life with Organizational Citizenship Behavior Keywords: personality, quality of work life, organizational citizenship behavior, servant leadership